2019
DOI: 10.1021/acs.jpcc.9b10871
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Intra- and Interband Transitions Associated with the Plasmon-Induced Hot Carrier Generation Process in Silver and Gold Nanoclusters

Abstract: In the last decades, theoretical and experimental studies of nanostructured materials have gathered the efforts of a big slice of the scientific community. Light−nanostructure interaction has been a preponderant research topic fueled by the interest in the plasmonic properties of metallic nanostructures. More recently, the study of plasmon-induced hot carrier generation has drawn the attention of scientists because of their potential application in optoelectronics, photovoltaics, and photocatalysis. In this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…1. It is important to highlight that the electronic structures provided by the DFTB Hamiltonian have proven to be suitable to study the bonded anatase and rutile TiO 2 nanocrystals, 45 the dynamics of plasmon-induced hot carrier generation in Au NPs, 30,31 and for predicting the photoinjection mechanisms in dye-sensitized TiO 2 solarcells. 46–48 The [Au-TiO 2 -CO] structure employed in this study is presented in the inset of panel b; it is a dimer formed by a 309 Au atoms icosahedral NP and an anatase TiO 2 NP (99 atoms).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. It is important to highlight that the electronic structures provided by the DFTB Hamiltonian have proven to be suitable to study the bonded anatase and rutile TiO 2 nanocrystals, 45 the dynamics of plasmon-induced hot carrier generation in Au NPs, 30,31 and for predicting the photoinjection mechanisms in dye-sensitized TiO 2 solarcells. 46–48 The [Au-TiO 2 -CO] structure employed in this study is presented in the inset of panel b; it is a dimer formed by a 309 Au atoms icosahedral NP and an anatase TiO 2 NP (99 atoms).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, this has been estimated in the order of hundreds of picoseconds 19,20 to nanoseconds, 21 challenging our interpretation of the problem and raising questions regarding the chemical catalysis mechanisms. 22 On the side of theoretical research, much effort has been invested to disentangle the hot-carrier generation process and their energy distribution in several plasmonic materials by means of many-body, 23–26 DFT, 6,27 TD-DFT, 28 DFTB 29–31 and phenomenological master equation techniques. 32–34 Interested readers can find comprehensive reviews of the latest experimental and theoretical advances in ref.…”
Section: Introductionmentioning
confidence: 99%
“…21 The latter can be used to access not only the absorption spectrum but the electron dynamics following excitation. 22 This method was succesfully used in the last decade to study the optoelectronic properties of a wide variety of organic and inorganic materials: the absorption spectra and photophysical properties of photosyntetic pigments 23,24 and DNA-protected silver emitters 25,26 , plasmonic properties of gold, 27-29 silver 28,29 and aluminium 30 metallic nanoparticles, optical properties of carbon-based materials like graphene nanoflakes 31 and graphene nanoribbons 32 and photoinduced charge transfer mechanisms elucidation in metal oxides [33][34][35][36][37] for dye-sensitized solar cells (DSSC) and molecular aggregates 38,39 for organic solar cells (OSC). These studies were performed within the electron-only quantum dynamics approach without considering nuclei movement, yet reaching a good agreement with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis has been conducted for noble metals in other recent reports. 5,11,15 The population and depopulation dynamics of ground state molecular orbitals (MO) are distinguished with positive and negative population values, indicating hot electron and hot hole generation, respectively. These MO population differences are calculated with respect to the ground-state population at the initial time t = 0 (∆ρ ii =ρ ii (t) − ρ ii (0)).…”
Section: Optical Absorption Spectra and Hot-carrier Distribution On Mg Nanoclustersmentioning
confidence: 99%
“…8 Recently, it has been reported that some plasmonic materials are able to effectively produce highly energetic distributions of electron-hole-pair (EHP) excitations upon non-radiative decay associated with dephasing of the plasmonic excitation (Landau damping). 5,[9][10][11][12][13][14] EHPs act as hot-carriers and can potentially promote bond formation/dissociation events in molecules adsorbed on or nearby the plasmonic material. This is often discussed in terms of two possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%